PENGEMBANGAN MEDIA PERMAINAN TEKA-TEKI SILANG ILMU PENGETAHUAN ALAM BERBASIS WEB UNTUK SISWA SEKOLAH DASAR - Tisrin Maulina Dewi; Dirneti; Fitria Meilina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to produce a web-based crossword puzzle game (TTS) media on natural science (IPA)subject for elementary school (SD) students. This media contained science practice questions for elementary school students equipped with web access so that students could use it during the online learning process at home. This research was development research that produced a game media. This study used a qualitative and quantitative descriptive design with research subjects including a) 2 material experts; b) 2 design experts; c) 6 elementary school teachers and d) 30 elementary school students. Qualitative data were obtained from observations, interviews, and input from the validator. Quantitative data were obtained from questionnaires given to validators and users. The questionnaire contained several statements according to the product being developed which consists of the feasibility of the material and the feasibility of the media display design. The results of this study indicated that: (1) the validation results from the material expert team and the design expert team respectively obtained a score of 84% and 86% in the very appropriate category and (2) the results of the teacher's response and the students’ test response obtained a score of 84% with the category very good. Thus, the web-based crossword puzzle game media was feasible and can be used as an additional alternative to teaching media in the learning process